Reminiscing the aesthetics and true functions of decoration in masjid - Zainal Abidin, Norzalifa (Noor Publishing, 2018)
“Arts are among the important and direct manifestation of the principles of the tradition, for men live in forms and in order to be drawn towards the Transcendent archetypes, they must be surrounded by forms that echo transcendent archetypes.”(Nader Ardalan, 1983). The role of decoration is one of the unifying factors in all buildings or objects from all over the Islamic world. The decorative principles of Islamic art can be applied to all types of building at all times (when the relationship between all applied arts and architecture). The decoration in the Islamic art especially the surface decoration in the Islamic architecture has a physical reality and visual impact which is independent and as important as their architectural forms. All of these visual effects are applied and enriched in carpet, cushion and also on ceiling or walls. The same decorative schemes are used for these decorations. Floors and ceiling contribute to the fluidity of space (Dalu Jones, 1987, p.161).